2020
DOI: 10.14807/ijmp.v11i7.1239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the effects of brand passion on commitment to brand through the adjusting role of ethics of brand

Abstract: Regarding the existence of different brands in the various fields of consumer products, customers’ commitment to the brand is an important factor in the success of the product of the brand. The present research studies the effects of brand passion on commitment to the brand with regard to the adjusting role of ethics of the brand. Regarding the goal of the study, research methodology applied is practical, and it is conducted as a survey. The research tool comprised three standard questionnaires; for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As a result, studies have shown that brands that can create and maintain deep emotional bonds (e.g., brand passion) with their customers may increase consumers' willingness to pay a price premium and positive word-of-mouth for the brand; additionally, it may increase brand engagement, purchase intentions, and brand loyalty, which are the ultimate goals of both marketing scholars and brand managers (Gilal et al, 2018). The investigation of the role of brand ethics in adjusting the effects of brand passion on brand commitment (Arayesh et al, 2020). The relationship between the variables of brand passion and brand commitment is significant, and brand ethics plays an important role in this relationship (Arayesh et al, 2020).…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, studies have shown that brands that can create and maintain deep emotional bonds (e.g., brand passion) with their customers may increase consumers' willingness to pay a price premium and positive word-of-mouth for the brand; additionally, it may increase brand engagement, purchase intentions, and brand loyalty, which are the ultimate goals of both marketing scholars and brand managers (Gilal et al, 2018). The investigation of the role of brand ethics in adjusting the effects of brand passion on brand commitment (Arayesh et al, 2020). The relationship between the variables of brand passion and brand commitment is significant, and brand ethics plays an important role in this relationship (Arayesh et al, 2020).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…The investigation of the role of brand ethics in adjusting the effects of brand passion on brand commitment (Arayesh et al, 2020). The relationship between the variables of brand passion and brand commitment is significant, and brand ethics plays an important role in this relationship (Arayesh et al, 2020). Brand passion and enjoyment are conceptualized as the affective cornerstones of the consumer engagement process, through which brands encourage their users to participate in brand communities and share their experiences.…”
Section: Theoretical Reviewmentioning
confidence: 99%